(untitled) (Global Journal of Medical Research, 2015)
Part of awell-designed health informatics simple mentation process includes the mechanisms put in place to help the day-to-day operators of the systems. Continual appraisal of these methods necessitates up-to-date investigations. Understanding critical elements which support a positive transition of health information technology (HIT) within healthcare facilities is the objective of the following research. To help develop these findings, a prospective postimplementation and use assessment survey was conducted on two hospitalsin Central Texas. The population studied included RN case managers, social workers and supportive staff in the Continuum of Care departmentsat two Scott & White Healthcare acute care facilities. The implementation process appeared to provide a mostly encouraging transition with a small number of components noted of concern to the staff. Areas of enhancement were revealed included improving training specific to job roles and supplying more fitting integration of processes and workflows.